Variants in CXCR4 associate with juvenile idiopathic arthritis susceptibility. Issue 1 (December 2016) - Finkel, Terri; Li, Jin; Wei, Zhi; Wang, Wei; Zhang, Haitao; Behrens, Edward; Reuschel, Emma; Limou, Sophie; Wise, Carol; Punaro, Marilynn; Becker, Mara; Munro, Jane; et al.
Abstract Background Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease among children, the etiology of which involves a strong genetic component, but much of the underlying genetic determinants still remain unknown. Our aim was to identify novel genetic variants that predispose to JIA. Methods We performed a genome-wide association study (GWAS) and replication in a total of 1166 JIA cases and 9500 unrelated controls of European ancestry. Correlation of SNP genotype and gene expression was investigated. Then we conducted targeted resequencing of a candidate locus, among a subset of 480 cases and 480 controls. SUM test was performed to evaluate the association of the identified rare functional variants. Results TheCXCR4 locus on 2q22.1 was found to be significantly associated with JIA, peaking at SNP rs953387. However, this result is subjected to subpopulation stratification within the subjects of European ancestry. After adjusting for principal components, nominal significant association remained (p < 10−4 ). Because of its interesting known function in immune regulation, we carried out further analyses to assess its relationship with JIA. Expression ofCXCR4 was correlated withCXCR4 rs953387 genotypes in lymphoblastoid cell lines (p = 0.014) and T-cells (p = 0.0054). In addition, rare non-synonymous and stop-gain sequence variants inCXCR4, putatively damaging for CXCR4 function, were significantly enriched in JIA cases (p = 0.015). Conclusion Our results suggest the association ofCXCR4 variants with JIA, implicating that this gene may be involved in the pathogenesis of autoimmune disease. However, because this locus is subjected to population stratification within the subjects of European ancestry, additional replication is still necessary for this locus to be considered a true risk locus for JIA. This cell-surface chemokine receptor has already been targeted in other diseases and may serve as a tractable therapeutic target for a specific subset of pediatric arthritis patients with additional replication and functional validation of the locus.